Antimicrobial Resistance, Pathogen Transmission and Cross-Infections across Regions and Borders: AMR, Pathogen Transmission and Cross-Infections within Regional Vicinity and across Borders - Aiman Bilal; Muhammad Esa; Zul Kamal; Bashir Ullah; Kashif Ali Khan; Sania Hameed; Muhammad Sohail; Anwar Ul Haq; Sara Khan; Fahmida Aslam (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Antimicrobial resistance is now considered a global dilemma and threat to many antibiotics running in clinical practices. In Pakistan, its worst consequences appear and rise day by day, especially in hospital and community-acquired healthcare settings. In Khyber Pakhtunkhwa (KP) especially in Peshawar, most of the Tertiary Care Hospitals, have a big flow of in and outpatients throughout the country as well across the border from Afghanistan, Iran, and Middle Eastern countries. So, the opportunities for cross infections, and transmission of Multidrug resistance/superbug strains are higher up, which needs to be assisted and evaluated. The current study was a combined prospective and retrospective nature study carried out in the endocrinology ward, in a tertiary care hospital in, Peshawar, KP, Pakistan. To ensure a thorough evaluation of treatment outcomes and the validity of the findings, the study attempted a combination of prospective monitoring and retrospective analysis to assess AMR, CSTs, and hospital stay longevity among 97 DFU inpatients. DFU was most prominent in the age range of 51-60 years, followed by 41-50 and patients above 60 years of age, respectively. Various antibiotics were prescribed to DFU patients. Among antibiotics, cefoperazone-Salbactam combination was highly prescribed (31.8%) followed by Linezolid (18.8%), and Ciprofloxacin and Meropenem (13.6% each). Patients having an age limit of 10-40 years were mostly resistant to antibiotic regimens including Ampicillin-clavulanic acid, cefipime, and cefoperazone-sulbactam. Similarly, patients in the age limit 41-50 were resistant to cefotaxime-sodium and ceftazidime. Furthermore, patients in the ages ranging 51-60 were resistant to co-trimaxazole, levofloxacin and moxifloxacin. In contrast, patients above the range of 61 years were found to be resistant to Ampicillin-clavulanic acid, cefipime, cefotaxime, ceftriaxone, co-trimaxazole, and levofloxacin. In conclusion, there is a strong need for comprehensive studies considering pathogen transmission, and cross-border infections in Pakistan to prevent the growing issue of AMR.